The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1097/01.mlg.0000205170.24517.28
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of Posttransplant Squamous Cell Carcinoma: The Potential Role of Cyclosporine A in Carcinogenesis

Abstract: Cyclosporine (CSA) is a widely used immunosuppressive agent, predominantly for transplant patients. It is well recognized that transplant patients are prone to develop squamous carcinoma of the skin and mucosa, and this high incidence of squamous carcinoma in the transplant population cannot be explained by immunosuppression alone. We hypothesize that CSA may play a significant role in the transformation of normal epidermal squamous cells to carcinoma. CSA is a specific ligand for calcineurin, a ubiquitously e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
2
7
0
1
Order By: Relevance
“…MMP‐26 may function to promote inflammation, 26 and this may influence the more aggressive phenotype of the SCCs of IS patients in addition to the fact that MMP‐26 is known to activate MMP‐9, one of the most critical MMPs in the growth of SCC 21 . Interestingly, MMP‐26 staining was significantly more intense in the tumors of patients using cyclosporine agreeing with recent Affymetrix data on a SCC cell line of the oral cavity 27 . That study showed in cell culture differential regulation of various MMPs after treatment with cyclosporine that not only functions as an immunosuppressant but also was shown to activate/inhibit genes important for cell cycle regulation, apoptosis and oncogene/tumor‐suppressor activation.…”
Section: Discussionsupporting
confidence: 86%
“…MMP‐26 may function to promote inflammation, 26 and this may influence the more aggressive phenotype of the SCCs of IS patients in addition to the fact that MMP‐26 is known to activate MMP‐9, one of the most critical MMPs in the growth of SCC 21 . Interestingly, MMP‐26 staining was significantly more intense in the tumors of patients using cyclosporine agreeing with recent Affymetrix data on a SCC cell line of the oral cavity 27 . That study showed in cell culture differential regulation of various MMPs after treatment with cyclosporine that not only functions as an immunosuppressant but also was shown to activate/inhibit genes important for cell cycle regulation, apoptosis and oncogene/tumor‐suppressor activation.…”
Section: Discussionsupporting
confidence: 86%
“…Although calcineurin inhibitors are excellent immunosuppressive agents to inhibit allograft rejection, they may promote the growth of different tumors (7, 9-11, 40). In this study, we define a mechanism in human cancer cells by which CsA can promote tumor growth through VEGF overexpression and angiogenesis, having direct relevance for the development of post-transplantation cancer.…”
Section: Discussionmentioning
confidence: 99%
“…In support of direct mechanism(s), it has been shown that the treatment of tumor xenografts in T- and B-cell deficient SCID mice with CNI enhanced tumor growth and progression (9). CNI may also activate/inhibit genes important for cell-cycle regulation, apoptosis, and oncogene/tumor-suppressor function (21). There are some reports that oncogenes may become activated in immunosuppressed transplant patients (2123).…”
Section: Introductionmentioning
confidence: 99%
“…CNI may also activate/inhibit genes important for cell-cycle regulation, apoptosis, and oncogene/tumor-suppressor function (21). There are some reports that oncogenes may become activated in immunosuppressed transplant patients (2123). However, very little is known about the signaling mechanism(s) of CNI-mediated direct tumorigenic pathways.…”
Section: Introductionmentioning
confidence: 99%